Review: Martin Nonhoff (2006). Politischer Diskurs und Hegemonie. Das Projekt "Soziale Marktwirtschaft" [Political Discourse and Hegemony. The Project "Soziale Marktwirtschaft"] - Schneider, Silke (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2007)
Following the thoughts of LACLAU and MOUFFEs hegemony theories, NONHOFF develops hegemony and hegemonic strategies as discoursive phenomena. He identifies core strategies which put political projects in hegemonic positions. For empirical prove of those core strategies, NONHOFF analyzes important texts and programmes concerning "Soziale Marktwirtschaft". Mainly in the theoretical parts of his book, NONHOFF develops convincingly a useful analytic structure for further studies of hegemony and discourse in political science.URN: urn:nbn:de:0114-fqs0702225